Can breast ultrasound reduce patient's level of anxiety and pain?. (May 2017) - Zarei, Fariba; Pishdad, Parisa; Hatami, Mohammad; Zeinali-Rafsanjani, Banafsheh
Background: Breast pain is one of the most common complaints of women attending a gynecology clinic and general practitioners. This pain can cause anxiety and, consequently, reduce the woman's quality of life. The objective of this study was to assess the severity of pain and anxiety in patients with breast pain and normal examination, before and after breast sonography. Materials and methods: Among the patients with breast pain and normal examination who came for breast sonography in three centers in Shiraz during 2011–2012, 51 patients agreed to cooperate in this project. These patients filled out the questionnaire for evaluation of pain and anxiety before and after breast sonography. Results: Sonography findings indicated that 88% of patients have normal sonography without any finding. The average amounts of pain severity before and after sonography were 3.3 and 2.4, respectively ( p < 0.005). The average amounts of anxiety severity in patients before and after sonography were 51.9 and 37.9, respectively ( p < 0.005). Conclusion: This study shows the severity of pain and anxiety after ultrasonography decreased significantly. It can be concluded that ultrasound findings, which reassure the patients that they do not have specific pathology, can reduce the pain and anxiety by its impact on psychological status of the patient.